Analisis Stabilitas Dinding Penahan Tanah Model Kantilever Sungai Sesaot Kabupaten Lombok Barat - Salehudin; Rohani; Hasyim (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2021)
The condition of the watershed (DAS) in the Sesaot forest area is still classified as good based on the assessment of the PALA method and the Flow Persistence Model. The Sesaot forest area is the upstream area of ​​the Jangkok sub-watershed. This analysis aims to obtain the results of the design of a retaining wall with a cantilever model with concrete and river stone materials with different height variations according to topographic conditions in each cross-section, as well as a Cost Budget Plan (RAB) with standard unit price analysis for the year area. 2021. Hydrological analysis shows that:, flood discharge using the Nakayasu method for a 100 year return period is 39,937 m3/s, with a maximum flood probability of 141,769 m3/s. Fragmental Method (Conventional Muskingum Method) with a cut-off distance of 20 km from the zero point of the watershed, overflowing flood over Spilwai Sesaot weir of 10.64 m3/s. Sectional analysis from STA 0 - 65 using retaining wall made of limestone, STA 65 to 100 retaining wall of cantilever type reinforced concrete with K225 quality. STA 100 - 400 type retaining wall combined between soil retaining wall type cage lever concrete and river stone. The amount of the budget plan is estimated at Rp.1,058,491,500.00 (One Billion Fifty-Eight Million Four Hundred Ninety-One Thousand Five Hundred Rupiah).